RasPBX 기반의 IP-PBX 시스템 - 정대진; 송현옥; 정회경; Jeong, Dae-Jin; Song, Hyun-Ok; Jung, Hoe-kyung (한국정보통신학회논문지, 2015)
VoIP and IP Telephony telephony technology development is a growing by easy to using IP-PBX by using phone from using existing lines rather than the internet. IP-PBX do not use the phone line from phone work for many companies and institutions of management costs reduce as provides similar to regular phone line quality. But IP-PBX to introduce for need to be the initial cost on is should buy for expensive hardware equipment or commercial software. In this paper, suggest way to introduce IP-PBX do not buy expensive hardware equipment or commercial software. Suggest IP-PBX on designed and implement for IP-PBX server using Raspberry Pi and Asterisk. And verification treatise on the suitability of conducted by voice calls based on IP-PBX between PC and a Smartphone VoIP(Voice over Internet Protocol)와 IP Telephony 기술이 발전함에 따라 기존 회선이 아닌 인터넷 망을 사용하여 전화를 사용하는 IP-PBX(Internet Protocol Private Branch Exchange)의 사용이 증가하고 있다. IP-PBX는 전화회선을 사용하지 않아 전화 업무가 많은 기업들과 기관들의 경영비용을 절감할 수 있으며 일반전화 회선과 유사한 품질을 제공한다. 하지만 IP-PBX를 도입하기 위해선 고가의 하드웨어 장비나 상용 소프트웨어를 구매해야 하는 초기 비용이 필요하다. 본 논문에서는 고가의 하드웨어 장비나 상용 소프트웨어를 구매하지 않고 IP-PBX를 도입할 수 있는 방안을 제안한다. 제안하는 IP-PBX는 Raspberry Pi와 Asterisk를 사용하여 IP-PBX 서버를 설계하고 구현한다. 그리고 구현된 IP-PBX 기반으로 PC와 스마트 폰 간의 음성 통화를 실시하여 논문의 적합성을 검증한다.